Local Geographical Differences in Adult Body Height in Montenegro - Stevo Popovic (Montenegrin Sports Academy, 2017)
The purpose of this research study is to examine body height in both Montenegrin sexes and map local geographical differences within both groups. A total of 2088 individuals (981 boys and 1107 girls) participated in this research study, and anthropometrical data were collected from 23 municipalities throughout the country. The anthropometric measurements were taken according to the ISAK protocol. Means and standard deviations were calculated for ages and anthropometric variable (body heights) as well as frequencies for the calculation of density of very short and very tall subjects. The results revealed that Montenegrin boys are 183.36±6.89 cm tall, while Montenegrin girls are 169.38±6.37 cm tall. The results of this study confirmed our assumption that both men and women in Montenegro are among the tallest people on the planet. However, the regional variation is considerable: from 181.25 cm in the municipality of Cetinje to 185.51 cm in the municipalities of Kolasin and Savnik for males and from 162.53 cm in the municipalities of Plav and Andrijevica to 170.86 cm in the municipality of Niksic for females. The measured values of body heights in Montenegro are currently one of the highest in the world, while the secular trend might increase it in the upcoming decades.